Kepemimpinan Kepala Sekolah dalam Membangun Hubungan dengan Orangtua Siswa di Madrasah Aliyah Swasta Kecamatan Medan Area Kota Medan - Neliwati; Rina Hidayah Tambusai; Carles Harahap; Cindi Gemilang (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Education plays a vital role in character formation and the development of the younger generation, including in Islamic education, which emphasizes moral and social values. In Madrasah Aliyah Swasta, Medan Area, the leadership of the principal is crucial in building positive relationships between the school and the parents. This study aims to analyze the principal's role in creating effective communication and encouraging parental involvement, as well as its impact on the quality of education. A qualitative research method with a case study approach was used, with data collected through interviews and observations. The findings show that open communication, both through regular meetings and digital media, as well as parental involvement in school activities, play an important role in fostering harmonious relationships and improving education quality. The principal acts as a facilitator who builds trust and collaboration between the school and parents. This study concludes that effective school leadership significantly impacts the quality of education in madrasahs.